(3SDGdGJ GdHQbGfi ddOGQ bWfis - (3GdHQbGfj , CMeO Hf eMeO Hf CMeO Hf ZGdH, CHh HcQ,J (B425 (3g` s ((3CHh HcQ Hf Ydi Hf ESeGYjd GdCfUGQi GdHgfSi GdTGaYi s)
(3ChdgG (B:s
(3gPg aUhd fbdJgG ef QbGY cfJ CKHJgG ajgG eeG SCdJ GdTjN CHG GdMSf Ydi Hf YeQ GdOGQ bWfi GdMGaX , afbdJgG HeG CLGHfi Yfg eG SCdJg ef Pdc , hQJHgG Ydi MQha GdeYLe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B74s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B82 s
Keywords: (3GdMOjK h GdeUWdMs